Casting process design and wear properties of a high chromium cast iron hammer (Engineering Review, 2017)
In this article, both chemical composition and structure of a high chromium iron hammer head were designed and analyzed respectively. Also, the casting process was investigated and optimized through numerical simulation using commercial software View Cast. On the basis of numerical simulation and optimization, several hammer heads with fine surface quality and no internal defects were cast into one mold through shell molding and string casting process. In addition, heat treatment of the as-cast hammer head was carried out. Consequently, the microstructure was observed, and wear resistance was tested. After being quenched at the temperature of 950? and tempered at the temperature in the range of 230-260?, the microstructure of the hammer is made up from tempered martensite, retained austenite and network eutectic carbides. The hardness is 60 HRC. Experimental result shows that the wear loss is slowly increased with an increase in load and rotating speed.